The characters of Elijah and Elisha and the deuteronomistic evaluation of prophecy: miracles and manipulation - Heller, Roy L. (Library of Hebrew bible/Old Testament studies, 2018)
Cover -- Half Title -- Title -- Copyright Page -- Dedication -- Contents -- Acknowledgments -- Abbreviations -- Chapter 1 Prophecy and Ambiguity -- A. The Question of Prophecy -- B. The Characters of Elijah and Elisha in Recent Research -- C. The Significance and Power of Ambiguity -- D. Deuteronomy and Prophecy -- 1. Deuteronomy 13:1-6 (ET 12:32-13:5) -- 2. Deuteronomy 18:15-22 -- E. The Ambiguous Character of Samuel -- F. The Question of Miracles -- Chapter 2 Narratives Focused on Elijah -- A. First Stories -- 1. Elijah Pronounces a Drought-1 Kings 17:1 -- 2. Elijah Cared for by Ravens-1 Kings 17:2-6 -- 3. Elijah Cared for by the Widow-1 Kings 17:7-16 -- 4. Elijah Restores the Widow's Son-1 Kings 17:17-24 -- B. Elijah and the Contest on Mount Carmel -- 1. Elijah's Instructions-1 Kings 18:1-2 -- 2. Elijah and Obadiah-1 Kings 18:3-16 -- 3. Elijah and Ahab-1 Kings 18:17-19 -- 4. The Contest on Carmel-1 Kings 18:20-40 -- 5. Elijah and Ahab and the End of the Drought-1 Kings 18:41-46 -- C. Elijah and the Theophany(?) on Mount Horeb -- 1. Elijah Flees from Jezebel-1 Kings 19:1-4a -- 2. Elijah Journeys Through the Wilderness-1 Kings 19:4b-9a -- 3. Elijah Complains to YHWH-1 Kings 19:9b-18 -- D. Elijah and the Meeting with Elisha-1 Kings 19:19-21 -- Excursus: Other Prophetic Stories at the End of 1 Kings -- E. Elijah and the Vineyard of Naboth-1 Kings 21 -- F. Elijah and the Illness of Ahaziah-2 Kings 1:1-18 -- G. The Evaluation of the Prophet Elijah-A Review -- Chapter 3 Narratives Focused On Elisha -- A. Elisha and Elijah Separate -- 1. Elijah Attempts to Leave Elisha Behind-2 Kings 2:1-8 -- 2. Elijah Is Taken Away-2 Kings 2:9-12 -- 3. Elisha and Elijah's Robe-2 Kings 2:13-14 -- B. Elisha's Small Tales-2 Kings 2:15-25 -- 1. Elisha and the Sons of the Prophets-2 Kings 2:15-18 -- 2. Elisha and Jericho's Water-2 Kings 2:19-22.